Synthesis, Photostudies, Biological Activity, Metal Complexes and Theoretical Study from New Schiff Bases Derived from 3-hydroxy Benzaldehyde and 1,3-Phenylene di amine - Kheder, Asmaa Y (Al-Nahrain Journal of Science, 2018)
Two new Schiff bases derived from 3-hydroxy benzaldehyde and 1,3-phenylene di amine have been prepared and identified by FTIR, UV. Spectroscopy and elemental analysis. The electronic spectra in ethanol, Benzene, dioxane, acetone and ethyl acetate were measured and interpreted. The metal complexes of these Schiff bases with divalent Cu, Co, Ni, Cd, trivalent Fe have been investigated by UV-visible spectrophotometry in neutral ethanolic solutions. One of these bases namly Bis-3-hydroxybenzaldene -N-N(1,3-phenylenediamine) (C20H16N2O2) was specific ligand to Co(II) as 1:1 propotion in addition to the biological activity and theoretical study using hyperchem program.